A p‐GaN‐Gated Hybrid Anode Lateral Diode with a Thicker AlGaN Barrier Layer. Issue 7 (8th March 2020) - Su, Shuai; Zhong, Yaozong; Zhou, Yu; Gao, Hongwei; Zhan, Xiaoning; Chen, Xin; Guo, Xiaolu; Sun, Qian; Zhang, Zihui; Bi, Wengang; Yang, Hui
Abstract : A p‐GaN‐gated hybrid anode lateral diode with a 45 nm‐thick AlGaN barrier is successfully fabricated through p‐GaN regrowth over recessed structure. This diode features a recessed p‐GaN‐gated ohmic hybrid anode, and the current flow from the anode to the cathode can be well controlled by the p‐GaN structure. With this architecture of regrown p‐GaN structure and thick AlGaN barrier, the forward turn‐on voltage ( V on ) and on‐resistance ( R on ) of the diode can be reduced simultaneously. Both V on and R on exhibit an excellent uniformity with an average value of 0.71 ± 0.02 V and 10.6 ± 0.27 Ω mm, respectively. Also, a high breakdown voltage (≈488 V) is achieved even in the absence of field plate structure. The fabrication process of the diode seems to be fully compatible with that of normally off high‐electron‐mobility transistors (HEMTs) with p‐GaN gate, which is successfully commercialized, enabling more convenient monolithic integration. Abstract : Herein, a successful fabrication of p‐GaN‐gated hybrid anode lateral diode with a 45 nm‐thick AlGaN barrier layer is reported. The diode performance of V on and R on can be improved by increasing the thickness of AlGaN barrier. Moreover, the fabrication process of the diode is compatible with that of normally off high‐electron‐mobility transistors with p‐GaN gate, enabling more convenient monolithic integration.